2016
DOI: 10.1111/bij.12799
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic but no genetic divergence in migratory and sedentary populations of blackcaps,Sylvia atricapilla

Abstract: In songbirds, territorial songs are key regulators of sexual selection and are learned from conspecifics. The cultural transmission of songs leads to divergence in song characteristics within populations, which can ultimately lead to speciation. Many songbirds also migrate, and individual differences in migratory behaviours can influence population genetic structure and local song differentiation. Blackcaps, Sylvia atricapilla, exhibit versatile territorial songs and show diversity in migration behaviours. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“… References: 1 Baker (); 2 Baker et al. (); 3 Balaban (); 4 González and Ornelas (); 5 Hafner and Petersen (); 6 Handford and Nottebohm (); 7 Leader, Geffen, Mokady, and Yom‐Tov (); 8 Linossier, Zsebők, Baudry, Aubin, and Courvoisier (); 9 Lipshutz et al. (); 10 Lougheed and Handford (); 11 MacDougall‐Shackleton and MacDougall‐Shackleton (); 12 Nicholls, Austin, Moritz, and Goldizen (); 13 Pavlova et al.…”
Section: Discussionmentioning
confidence: 99%
“… References: 1 Baker (); 2 Baker et al. (); 3 Balaban (); 4 González and Ornelas (); 5 Hafner and Petersen (); 6 Handford and Nottebohm (); 7 Leader, Geffen, Mokady, and Yom‐Tov (); 8 Linossier, Zsebők, Baudry, Aubin, and Courvoisier (); 9 Lipshutz et al. (); 10 Lougheed and Handford (); 11 MacDougall‐Shackleton and MacDougall‐Shackleton (); 12 Nicholls, Austin, Moritz, and Goldizen (); 13 Pavlova et al.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between the two estimates (Pearson’s correlation, r = 0.8, df = 318, P < 10 –15 ) indicated that the k-means clustering method serves as a reliable surrogate for repertoire size. Therefore, to estimate the repertoire size in our study, we calculated the number of k-mean clusters that could be detected for a given individual based on 20 songs (see also Linossier et al 2016 ). We also calculated song rate (the number of songs in a minute calculated as 60/median of song intervals), which inherently corresponded to the same hierarchical level.…”
Section: Methodsmentioning
confidence: 99%
“…Internal factors such as body size (Linossier et al, 2016;Rolandsen et al, 2017;Strait et al, 2021) and breeding status (Hegemann et al, 2015;Thériault et al, 2007), drive migration in some species. Internal factors are likely influenced by a combination of genetic variation and an animal's external environment.…”
Section: Introductionmentioning
confidence: 99%